CREDIT RISK MANAGEMENT CONTROL ON SME SEGMENT: STUDY CASE OF XYZ BANK BRANCH SURABAYA - Mayasari, Ludmila; Harianto, Eric; Albazi, Uzair; Nursaid, Nursaid; Mas’ud, Riduan (Universitas Brawijaya, Indonesia, 2022)
The study is conducted to explain the suitability of credit risk control management to minimize the non-performing loans at XYZ Bank Branch Surabaya as stipulated by the Basel Accord Committee in Financial Services Authority Regulation No. 18/PJOK.03/2016 about the Implementation of Risk Management for Commercial Banks. Based on the Basel III guidelines, credit risk management includes seven mechanisms. The seven mechanisms are the policy framework, credit risk rating framework, credit risk limits, credit risk modeling, credit risk mitigation, credit audits, and loan review mechanisms. The study uses a qualitative study by the case study approach. The results showed that the control of credit risk management implemented by Bank XYZ Surabaya Branch to minimize non-performing loans to individual debtors in the SME segment had not run effectively. It was primarily about the evaluation of credit risk, which led to the emergence of a new set of risks such as errors in credit risk evaluation, target market losses and ineffective allocation of loan funds, and inadequate strategies for collecting net credit to customers. The study also provides several recommendations for credit risk management as the strategy to reduce the risk of lending to individual debtors in the SME segment at XYZ Bank Branch Surabaya.